Religious Moderation in Indonesia's Multicultural Society: A Conceptual and Social Analysis - Arna Saskia; Rahmad Hidayat; Jamilus; Kumaidi; Novita Jurniati (al-Afkar, Journal For Islamic Studies, 2026)
Indonesia is a country characterized by a high level of religious, ethnic, and cultural diversity, which necessitates a religious approach capable of maintaining social harmony and cohesion. Religious moderation has emerged as an essential concept in responding to such pluralism by emphasizing balance, tolerance, and justice in understanding and practicing religious teachings. This article aims to examine the concept of religious moderation, its foundations and underlying principles, its core values, objectives and urgency, forms of implementation, as well as the supporting and inhibiting factors within the Indonesian social context. This study employs a qualitative approach using a literature review method, analyzing scholarly books, peer-reviewed journal articles, and relevant policy documents. The findings indicate that religious moderation is grounded in strong theological, philosophical, and constitutional foundations and plays a strategic role in preventing conflict, strengthening humanitarian values, and maintaining national integration. The implementation of religious moderation requires sustained collaboration among the government, educational institutions, religious leaders, and society. Despite challenges such as radicalism, limited digital literacy, identity politics, and the lack of exemplary leadership, religious moderation remains a fundamental pillar in fostering a peaceful, just, and tolerant society in Indonesia.